The Shape of a Hole is Perceived as the Shape of its Interior. (October 2014) - Nelson, Rolf; Reiss, Jason E; Gong, Xue; Conklin, Sherri; Parker, Laura; Palmer, Stephen E
In typical figure–ground displays the figure has shape and is perceived as being in front, whereas the ground is shapeless and recedes to the back. The recent literature on the visual perception of holes has questioned the nature of this coupling between shape and depth both theoretically and empirically. In this paper we provide a theoretical framework that clarifies the underlying issues and we report new evidence supporting the view that the shape of a hole is perceived as the shape of its interior region. Palmer, Davis, Nelson, and Rock (2008 Perception, 37, 1569–1586) showed that the shape of the interior region of a hole is remembered as such, even though the surface visible through it is perceived as farther in depth. The present paper extends this evidence to perceiving holes. Participants performed a speeded shape-matching task in which they compared a surrounded interior region (of either a hole or an object) or its exterior complement with one of several shapes. The results indicate that holes are perceived as shaped in the same way as their material counterparts. We conclude that the shape of a hole is encoded as the shape of its interior region, even though that region contains no surface material. These results can be reconciled with recent experiments that have provided evidence that holes are perceived differently from their material counterparts.